Management Accounting Information Quality and Its Effect on Managerial Performance in Innovative Enterprises - Siti Hajar (Journal of Business Innovation and Accounting Research, 2026)
This study investigates the relationship between management accounting information quality and managerial performance within innovative enterprises operating in Malaysia. Management accounting systems serve as critical organizational control mechanisms that provide managers with essential information for decision-making and reducing environmental uncertainty. Drawing upon contingency theory, this research examines how the characteristics of management accounting information—specifically scope, integration, aggregation, and timeliness—influence managerial performance outcomes in the Malaysian context. A quantitative research methodology was employed, utilizing structured survey questionnaires distributed to managers in innovative enterprises across Malaysia. The findings reveal that management accounting information quality significantly and positively affects managerial performance, with innovation performance serving as a moderating variable in this relationship. The study contributes to the existing literature by providing empirical evidence from Malaysian innovative enterprises, demonstrating that high-quality management accounting information enables managers to make better decisions, enhance organizational control, and ultimately improve performance outcomes. The implications suggest that innovative enterprises should invest in developing comprehensive management accounting systems that provide timely, integrated, and broad-scope information to support managerial decision-making processes.